Synthetic Biology and the Boost of COVID-19 Vaccines Technology Development through International Alliances - Muñoz-Miranda, Luis Alfonso; Arreola-Hernández, Ana Sofía; Figueroa-Yáñez, Luis Joel (CIENCIA ergo-sum; Vol. 29 Núm. 4 (2022): Número especial “SARS-CoV-2” (segunda parte)DO - 10.30878/ces.v29n4a5, 2022)
The importance of the development of the necessary technology to achieve the production of vaccines from a “synthetic biology” perspective is analyzed, as well as the essential articulation and financing through international cooperation to combat COVID-19, all the information on this topic is from the bibliographical research on topics focused on the development, cooperation, and international regulations involved in the synthesis of COVID-19 vaccines. A comprehensive vision on the recent development strategies on health and bioeconomy issues is proposed to face future eventualities and thus promote better health-oriented developments with the possibilities of immediate action.